Which forecast represents the local weather best?: Preliminary case study findings from My Loi village, northcentral Vietnam - Roy, Antika; Simelton, Elisabeth; Quinn, Claire (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
All three forecasts under-predicted temperatures, while AccuWeather overestimated and Windyty underestimated the total rainfall (for the two months, by 100 mm); however no systematic error could be determined to reduce the error.  As uncertainties are rapidly increasing with longer lead time than two days ahead, the researchers advise to follow several forecast sources to get a range of scenarios.